Osteology of Atelopus muisca (Anura, Bufonidae) from Colombia - Hoyos, Julio Mario; Medina, Paola; Schoch, Paulette (Zootaxa, 2015)
The first comprehensive description of the skeleton of Atelopus muisca Rueda-Almonacid & Hoyos, 1991 (Bufonidae, Anura) from the Chingaza Natural National Park (Colombia) is provided, and comparisons with some characters described for this species by Coloma and related frogs of the group A. ignescens are done. The humerus of male presenting more developed crista ventralis and crista lateralis, and the articulation of the frontoparietal bones showed the presence of sexual dimorphism. These are character not described for species of the genus Atelopus belonging to the group A. ignescens. A. ignescens. Among the other osteological characters we did not find unique feature for the species.